ANALISIS EFEK KEPUASAN PASIEN SEBAGAI PEMBENTUK NIAT MENGGUNAKAN PENDAFTARAN PASIEN BERBASIS WEBSITE - Rahmawati, Ayu; Setyawan, Didik; Noor, Finisha Mahaesti (Fakultas Ekonomi - Universitas Setia Budi, 2019)
This study aims to test the behavior of the intention to use the system information that is formed from the intention of the patient's behavior towards the satisfaction of which is influenced by expediency, perceived usefulness, and credibility which are perceived society in while using the registration-based website. Sampling technique was purposive sampling with the population of the community in Solo using the application 's E-Patient. The results of this study indicate all supported hypothesis. These results credibility registration-based that to form the Intention of the patient's Behavior in the use of the means website registration through the expediency of perceived usefulness, and credibility which are perceived.